2022
DOI: 10.3389/fnut.2022.807344
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Causal Relationship Between Vitamin D Status and Risk of Psoriasis From the UK Biobank Study

Abstract: BackgroundPlenty of observational studies suggested that vitamin D concentrations were associated with psoriasis, but the causality of this relationship was elusive.ObjectiveTo investigate the causal relationship between vitamin D and psoriasis.MethodsCox proportional hazard model was used to investigate the association between vitamin D status and psoriasis in a prospective cohort study from UK Biobank. Single nucleotide polymorphisms (SNPs) that are strongly associated with circulating 25OHD were constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…A recent US study suggested a preventive effect of vitD supplements on autoimmune disease risk . Moreover, a recent mendelian randomization study found evidence of a causal relationship between genetically predicted lower 25(OH)D levels and incident psoriasis . Therefore, vitD may contribute to prevention and treatment of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent US study suggested a preventive effect of vitD supplements on autoimmune disease risk . Moreover, a recent mendelian randomization study found evidence of a causal relationship between genetically predicted lower 25(OH)D levels and incident psoriasis . Therefore, vitD may contribute to prevention and treatment of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Administrating vitamin D supplementation led to reduced mortality in patients with psoriasis [17] and topical vitamin D analogues demonstrated effectiveness in treating psoriasis [9]. A recent prospective study suggested that low 25(OH)D level was associated with high risk of psoriasis using both cox proportional hazard model and MR analysis [27]. It used 69 genetic variants that were identified in a GWAS meta-analysis of 443,734 European individuals as IVs in the MR analysis [45].…”
Section: Discussionmentioning
confidence: 99%
“…Recent genome-wide association studies (GWASs) have identified tens of thousands of genetic variants robustly associated with human complex diseases and traits [24], which as a result provide a wealth of potential IVs and facilitate MR analysis. MR analyses have investigated the causal effects of circulating 25(OH)D levels on the risk of psoriasis, atopic dermatitis, and vitiligo, suggesting that blood 25(OH)D levels confer a significant causal effect on psoriasis but not on atopic dermatitis or vitiligo [25][26][27]. Alternatively, MR suggests that genetically predicted risk of atopic dermatitis increases blood 25(OH)D level [28].…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies has found an association between lower serum 25-hydroxyvitamin D (25[OH]D) and psoriasis 13 . MR studies have additionally demonstrated a causal relationship from lower 25(OH)D to an increased risk of psoriasis 14,15 . Moreover, no reverse causal link has been observed 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent observational studies suggest that the association between 25(OH)D and psoriasis may be modified by adiposity (BMI and hip-waist ratio) 14,17,18 . No previous studies have explored this possible combined effect (i.e.…”
Section: Introductionmentioning
confidence: 99%